Кодові криптосистеми для постквантового застосування - Кузнецов, Олександр Олександрович; Пушкарьов, Андрій Іванович; Горбенко, Юрій Іванович (Kamianets-Podilskyi National Ivan Ohiienko University, 2017)
Code-based public-key cryptosystems based on algebraic coding are considered. They are based on masking algebraic block codes with fast decoding algorithm (polynomial complexity) at random linear block code with NP-hard decoding. Assessment the strength is offered, including quantum cryptanalysis, and evaluating performance in comparison with the known cryptosystems.